E-books in libraries [ - Tedd, Lucy A. (Bradford, England : Emerald, 2007)
In May 2007 a one-day seminar on "Putting content in context" at University College London stated in its introductory information, "E-books have finally become accepted in many organizations and licensed e-content is proliferating through library catalogues and web portals." The development of electronic versions of printed books (or e-books) can be seen as part of the whole e-publishing phenomenon that began in the 1960s. E-books are fast becoming a central part of the modern library, and thus the practical issues surrounding their use must be considered. This e-book brings together a number.
1. Cover -- 2. CONTENTS -- 3. EDITORIAL ADVISORY BOARD -- 4. Editorial; Cataloguing e-books in UK higher education libraries: report of a survey -- 5. E-books from MyiLibrary at the University of Worcester: a case study -- 6. The Safari e-book route through the ICT jungle: experiences at Hillingdon Libraries -- 7. Managing e-books at the University of Derby: a case study -- 8. E-books from ebrary at Staffordshire University: a case study -- 9. The online reading list project using Talis List at the University of Glamorgan -- 10. Desa Informasi: a virtual village of "new" information resources and services in Indonesia
Title from PDF caption (viewed Nov 28, 2007)
Includes bibliographical references
Keywords: Electronic books